2016
DOI: 10.1080/1028415x.2016.1149294
|View full text |Cite
|
Sign up to set email alerts
|

Effects of cafeteria diet and high fat diet intake on anxiety, learning and memory in adult male rats

Abstract: According to those data it was concluded that hypercaloric diet ingestion was capable of triggering metabolic alterations and possibly lowering anxiety associated to learning or memory improvement on a spatial task.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(11 citation statements)
references
References 24 publications
0
10
0
1
Order By: Relevance
“…This factor should be considered with the context of both the induction of food intake caused by variety (and novelty) of foods and tastes ( Moore et al, 2013 ), which in part exploits the “explorative” drive shared by rats and humans. In addition, the intake of pleasing food (such as sweets), lowers the levels of anxiety ( Faturi et al, 2010 ), and is used (by humans and experimental animals alike) as “comfort food” ( Ortolani et al, 2011 ) to escape of conflict situations, or simply for pleasure ( Pini et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This factor should be considered with the context of both the induction of food intake caused by variety (and novelty) of foods and tastes ( Moore et al, 2013 ), which in part exploits the “explorative” drive shared by rats and humans. In addition, the intake of pleasing food (such as sweets), lowers the levels of anxiety ( Faturi et al, 2010 ), and is used (by humans and experimental animals alike) as “comfort food” ( Ortolani et al, 2011 ) to escape of conflict situations, or simply for pleasure ( Pini et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…Cafeteria diets have been widely used to fatten rats, but a number of Authors tend to consider that the variability attributed to self-selection by taste may be a serious handicap of this model ( Moore, 1987 ). Cafeteria diets are very effective creating a model of metabolic syndrome ( Gomez-Smith et al, 2016 ), which can cause oxidative damage in adipose tissues ( Johnson et al, 2016 ), although it also lowers the anxiety of rats ( Pini et al, 2016 ) attenuating their response to stress ( Zeeni et al, 2015 ) because of the “comfort food effect” ( Ortolani et al, 2011 ). On the other hand, the analysis of what food items were selected by the rats is laborious, but the results obtained are precise, and may allow us to measure the change with exposure time during different phases of development ( Prats et al, 1989 ; Lladó et al, 1995 ).…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have already shown that palatable diets can promote anxiolytic states, as well as attenuate anxiogenic conditions originating from stressors in the prenatal and postnatal stages in rodents 36,37 . In a study by Pini et al 38 , male Wistar rats who were treated with a cafeteria diet from weaning until adulthood showed lower anxiety levels than the control diet group.…”
Section: Weaning To Adulthood (D21-d70)mentioning
confidence: 96%
“…A majority of, but not all (Nguyen et al., 2017; Pini et al., 2017), rodents studies suggests that CD feeding interferes with hippocampus mediated spatial learning (Beilharz et al., 2014; Ferreira et al., 2018; Kendig et al., 2019; Kosari et al., 2012; Tran & Westbrook, 2015) but functioning of other brain structures can also be affected (Nguyen et al., 2017). Two different pathways have been described for underlying either object recognition memory or spatial and hippocampal memory although both require PFC, albeit different substructures of the PFC, functioning (Barker et al., 2007; Steckler et al., 1998).…”
Section: Discussionmentioning
confidence: 99%